Proszę o rozwiązanie równań
-9(3y-2)-4(5-6y)=0 a wynik to y=-⅔
5y=4+5(2y-3)-6(3y-4) wynik y=1
6[2-3(2x-5)]-5(1-2)=7-2(11x-5) wynik x=20
3(2x+1)=10x-0,6
0,2(1-0,3x)=0,04x+1
-2,5(0,4x-0,1)=4(1+0,5x)
i jeszcze zadanie z ksiazki do 1 gim (zielona)3 na 176

2

Odpowiedzi

  • Użytkownik Zadane
2010-03-14T19:49:29+01:00
-9(3y-2)-4(5-6y)=0
-27y+18-20+24y=0
-3y-2=0
-3y=2
y=-⅔

5y=4+5(2y-3)-6(3y-4)
5y=4+10y-15-18y+24
5y=-8y+13
13y=13
y=1



3(2x+1)=10x-0,6
6x+3=10x-0,6
-4x=2,4
x=-0,6

0,2(1-0,3x)=0,04x+1
0,2-0,06x=0,04x+1
-x=0,8
x=-0,8

-2,5(0,4x-0,1)=4(1+0,5x)
-x+0,25=4+2x
-3x=3,75
x=-1,25
Najlepsza Odpowiedź!
2010-03-14T19:54:21+01:00
-9(3y-2)-4(5-6y)=0
-27y+18-20+24y=
-3y=-18+20
-3y=2 ||:(-3)
y=-⅔

5y=4+5(2y-3)-6(3y-4)
5y=4+10y-15-18y+24
5y-10y+18y=4-15+24
-5y+18y=-11+24
13y=13 ||:13
y=1

6[2-3(2x-5)]-5(1-2)=7-2(11x-5)
6(2-6x+15)-5+10=7-22x+10
12-36x+90-5+10=7-22x+10
107-36x=17-22x
107-17=-22x+36x
90=14x ||:14
x=6

3(2x+1)=10x-0,6
6x+3=10x-0,6
6x-10x=-0,6-3
-4x=-3,6||:(-4)
x=0,9

0,2(1-0,3x)=0,04x+1
0,2-0,06x=0,04x+1
-0,06x-0,04x=1,2
-0,1x=1,2 ||:(-0,1)
x=-12

-2,5(0,4x-0,1)=4(1+0,5x)
-x+2,5=4+2x
-3x=1,5 ||:(-3)
x=0,5